Exploring long-term impacts of different crop rotation systems on sustainable use of groundwater resources using DSSAT model. (15th February 2022) - Gao, Fei; Luan, Xiaobo; Yin, Yali; Sun, Shikun; Li, Yi; Mo, Fei; Wang, Jiahui
Abstract: Groundwater depletion has been a global concern due to unreasonable agricultural water managements. Identifying long-term impacts of crop rotation systems on hydrological parameters and crop yields can help to alleviate groundwater depletion. The Decision Support System for Agro-technology Transfer model was applied to simulate impacts of nine crop rotation systems (H1: continuous spring maize; H2: continuous potato; H3: continuous spring wheat; H4:potato-maize rotation; H5:maize-wheat rotation; H6: wheat-potato rotation; H7: two year fallow-maize rotation; H8: two year fallow-potato rotation; H9: two year fallow-wheat rotation) on crop evapotranspiration, percolation, yields, water use efficiency, net water use and groundwater table depth changes in Zhangjiakou, China from 1985 to 2018. The results showed DSSAT model performed well in simulating crop ET, yields (R2>0.9, RMSE<500 kg ha −1 ) and soil water content (R2>0.9 and RMSE<10.1 mm). The long-term two year fallow with one single crop rotation systems (H7 to H9) had lower total accumulative groundwater table depth changes (2.8–14.4 m) than others (12.7–52.3 m) from 1985 to 2018. Also, cropping rotation systems H7 to H9 obtained the lower annual average net water use (14–70 mm) compared to other cropping rotation systems (62–253 mm). The significant difference of net water use, crop yields, water use efficiency and accumulative groundwater table depth changes of nine different cropping systems indicated H4 and H8 is suitable in the study region. Our results is useful for selecting suitable cropping systems based on the water use for local farmers. Graphical abstract: Image 1 Highlights: Effects of cropping systems on groundwater were well simulated by DSSAT model. Water-saving effect is different within different crop rotations. Two year fallow with one single crop rotation alleviates groundwater decline.